Respuesta :

Answer:  see proof below

Step-by-step explanation:

Given: A + B + C = π                    →    A + B = π - C

                                                    →    A + C = π - B

Use the Cofunction Identities:   sin (π - A) = sin A

                                                    sin (A - π/2) = cos A

                                                    cos (π/2 - A) = - sin A

Use the Power Reducing Identity:  sin ² A - sin² B = sin (A + B) · sin (A - B)

Use the Sum to Product Identity:

                                               sin A - sin B = 2 [cos (A + B)/2] · [sin (A - B)/2]

Proof LHS → RHS:

LHS:                                   sin² A - sin² B - sin² C

                                       = (sin² A - sin² B) - sin² C

Power Reducing:           sin (A + B) · sin (A - B) - sin² C

Given:                             sin (π - C) · sin (A - B) - sin² C

Cofunction:                    sin C · sin (A - B) - sin² C

Factor:                            sin C [sin (A - B) - sin C]

[tex]\text{Sum to Product:}\qquad \sin C\bigg[2\cos \bigg(\dfrac{(A-B)+C}{2}\bigg)\cdot \sin \bigg(\dfrac{(A-B)-C}{2}\bigg)\bigg]\\\\\\.\qquad \qquad \qquad \qquad =2\sin C\bigg[\cos \bigg(\dfrac{(A+C)-B}{2}\bigg)\cdot \sin \bigg(\dfrac{A-(B+C)}{2}\bigg)\bigg][/tex]

[tex]\text{Given:}\qquad \qquad 2\sin C\bigg[\cos \bigg(\dfrac{(\pi - B)-B}{2}\bigg)\cdot \sin \bigg(\dfrac{A-(\pi - A)}{2}\bigg)\bigg]\\\\\\.\qquad \qquad \qquad =2\sin C\bigg[\cos \bigg(\dfrac{\pi -2B}{2}\bigg)\cdot \sin \bigg(\dfrac{2A-\pi}{2}\bigg)\bigg]\\\\\\.\qquad \qquad \qquad =2\sin C\bigg[\cos \bigg(\dfrac{\pi}{2} -B}\bigg)\cdot \sin \bigg(A-\dfrac{\pi}{2}\bigg)\bigg][/tex]

Cofunction:             2 sin C (-sin B) · (cos A)

                           = -2 sin C · sin B · cos A

                           = -2 cos A · sin B · sin C

LHS = RHS:   -2 cos A · sin B · sin C = -2 cos A · sin B · sin C  [tex]\checkmark[/tex]

Ver imagen tramserran
Ver imagen tramserran